Frequency of Oral Lesions in Diabetic Patients on Oral Hypoglycemic Drugs and Insulin - Sanaa Ahmed, Hina Shah, Juwariah Sohail, Saba Rizwan, Sadia Khalil, Mohsin Rizvi (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Lichen planus is a pre-cancerous condition which is immune mediated. It is often linked with other autoimmune diseases such as Diabetes Mellitus. It is linked with both Type 1 and Type 2 DM. Methods: A retrospective cross-sectional study that was conducted at Jinnah Sindh Medical University on data of patients coming to Oral Medicine OPD from January 2020- December 2022. Diabetic patient`s data was extracted, and secondary analysis was done on it to find out the frequency of the lesions in both types. Results: Data of 211 patients were analyzed through SPSS ver. 20. Total of 30 patient with oral lesions presented with diabetes mellitus with 8 having hepatitis c. Data was excluded of those with co-morbid. The predominant age group was 41-50 years, all males, presenting with type 2 DM. Gingivitis(N=10) was the commonest followed by Oral Lichen Planus(N=7), Periodontitis(N=3), and Infections(N=2).The lesions were predominant in patients on Glucophage and insulin. Conclusion: Diabetes Mellitus predisposes patients to a variety of oral problems. Early diagnosis of these lesions and changes in medication as per requirement to treat these lesions may benefit the quality of life of these patients. Keywords: Oral Lichen Planus, Diabetes Mellitus, Autoimmune disorder